Mudanças climáticas e conservação de peixes de água doce - Peluso, Luiza Moura (2022)
Climate change in progress is one of the main threats to freshwater fish and ecosystems. In response to variable climate and extreme weather events, fishes can modify their ecology, which also affect activities dependent on this resource. The Pantanal, the largest wetland in the world, is situated in the center of the Upper Paraguay River Basin (UPRB) and is a biome highly dependent on the flood pulse to maintain high biodiversity, including fish diversity. For functionally and maintenance of this watershed it is necessary to ensure hydrological connectivity between the Planalto (plateau) and the Pantanal plain. In the UPRB, fishes play role ecological functions in the aquatic habitats, and it is also food and income for traditional populations. Considering that future conditions in the UPRB will be warmer and drier, in this thesis we assess the potential effects of current threats on patterns of freshwater fish diversity and identify geographic and taxonomic biases of existing protected areas in the UPRB. In the first chapter, we assessed the climate change effects and potential impacts of river fragmentation by dams under migratory fishes. The fish climatic niche will reduce over time and the loss of suitable habitat may be greater due to rivers blocked by dams. In the second chapter, we evaluated the climate change effects on alpha and beta diversity patterns for a larger suite of UPRB fish species, identifying possible locations where there will be greater species loss and change. In the third chapter, we assess the conservation status of fish species and to what extent are these species are sheltered by the current network of protected areas. Among the species evaluated, 24% of fish species were classified in some extinction risk and the most of them are outside the protected areas. Finally, in the fourth chapter we showed the implications of the new Pantanal Law on land use change in the biome. We expect that our results to direct and support conservation strategies because conserving freshwater ecosystems and fish biodiversity is a challenge in the front of the threat processes.